Introducing cultural and media studies a semiotic approach - Davis, Lloyd 1959-2005; Mules, Warwick (Palgrave Macmillan, 2002)
It adopts a practical and versatile approach to cultural analysis, beginning not with an abstract body of theory but with a number of examples of social sign use which are examined critically using basic semiotic terms and concepts to build up the reader's analytic vocabulary in a practical way.